Pulmonary tuberculosis in clinical practice - A. T. Shubina; E. A. Borodulina; A. N. Gerasimov; E. V. Yakovleva (Сибирский научный медицинский журнал, 2021)
Pulmonary tuberculosis has a lot of clinical manifestations, and it complicates the diagnosis of tuberculosis in the general clinical practice. We studied the clinical manifestations of tuberculosis detected in the pulmonary department and compared them with the significancy of diagnostic methods.Material and methods. People with a verified diagnosis of lung tuberculosis (n = 109) were examined using the GeneXpert MTB/RIF method if Ziehl Nielsen bacterioscopy has negative results or if there was no effect of treatment for two weeks.Results. All patients had complaints of both intoxication and bronchitis as with pneumonia on admission. Infiltrative tuberculosis (57.1 %; n = 68), disseminated tuberculosis (16.8 %; n = 20) were most often diagnosed. We looked for correlations between dyspnea and the prevalence of the process (p = 0.24), dyspnea with temperature (p = 0.24), the presence of pain in the chest (p = 0.405), the results of immunodiagnostics and sputum examination (p = 0.133). We found out that there are no such correlations in tuberculosis. The term for diagnosing tuberculosis was 7.97 ± 3.9 days in the presence of cough with sputum and 9.04 ± 4.3 days in the case of dry cough. The term for diagnosing tuberculosis was 12.31 ± 4.9 days in patients without cough. Mycobacterium tuberculosis was detected using GeneXpert MTB/RIF molecular genetic methods with nonproductive cough in 84.5 % (60 people out of 71), while in the first days of hospitalization in 46.6 % of patients (28 people out of 60, p < 0.001).Conclusion. It was found that the period of hospitalization is little related to the characteristics of patients and depends on organizational measures to identify mycobacterium tuberculosis. It is recommended to immediately apply the GeneXpert MTB/RIF method to patients with mild tuberculosis.